Grass species litter have varied trait response to the photodegradation and microbial decomposition in tropical savanna grasslands, South Africa - Mmoto L Masubelele; William Bond (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Purpose of the paper: This paper evaluated the effects of microbial and photodegradation on the ten grass species in a tropical grassland ecosystem in South Africa. Despite continuous necromass accumulation in tropical grasslands, the process that governs how the grass litter gets to the soil has often been ignored. In the absence of fire, abiotic factors and biotic factors are drivers of this process of nutrient cycling.  Methods and approaches: A classical litterbag experiment was set up to simulate photodegradation (standing litter) versus microbial (soil surface) decomposition using 10 savanna types of grass from the start of the dry season until the beginning of spring. The rates of photodegradation versus microbial decomposition were compared for tropical savanna grasses and plant traits or predictors of decomposition were also investigated.  Main results: The results showed that the grass litter decomposed more rapidly when exposed to the activity of soil microbes at the soil surface (k = 0.0028 ) than when held above ground (k = 0.0018) and subjected to photodegradation only. However, examination of the individual litter species revealed up to 4 fold variation between the slowest (0.0001) and fastest (0.006) decomposing species. Differences in decomposition rates were more pronounced for litter decomposed at the soil surface than held above the soil surface. Multiple linear regression analyses did not resolve clear differences between measures of litter quality as drivers of decomposition in the two treatments.  Implications: Photodegradation appeared to be a rate-controlling step during the process of decomposition in tropical savanna grasslands. Therefore grasslands dominated by photodegradation-resistant grasses were likely to need fire to get rid of moribund litter, which may be the reason why mesic grasslands need to burn to recycle nutrients.